If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -3) + 4 = 2(x + -4) Reorder the terms: 5(-3 + x) + 4 = 2(x + -4) (-3 * 5 + x * 5) + 4 = 2(x + -4) (-15 + 5x) + 4 = 2(x + -4) Reorder the terms: -15 + 4 + 5x = 2(x + -4) Combine like terms: -15 + 4 = -11 -11 + 5x = 2(x + -4) Reorder the terms: -11 + 5x = 2(-4 + x) -11 + 5x = (-4 * 2 + x * 2) -11 + 5x = (-8 + 2x) Solving -11 + 5x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -11 + 5x + -2x = -8 + 2x + -2x Combine like terms: 5x + -2x = 3x -11 + 3x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -11 + 3x = -8 + 0 -11 + 3x = -8 Add '11' to each side of the equation. -11 + 11 + 3x = -8 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = -8 + 11 3x = -8 + 11 Combine like terms: -8 + 11 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 12x^2+17x-7=0 | | 5x+10=2(2x+5) | | (2a/3)+(7a/9)+2=0 | | 4y-20= | | -3kx^2+4x^2+26x-17=0 | | 11=x-4 | | 4a+13-a+7=7a+10+2-a | | 3x^2+5x-50=0 | | 11x=90-7x | | 12z/3=z-6 | | x-3/5=-1/2 | | 5y-3(y-2)+4= | | 55=(x+25) | | 5x+12=7x-8 | | 20+5x=4(x-3) | | 4x+10=100 | | 9y-47=y+73 | | 105+(3x-18)=180 | | 0=x^2+12x-6 | | -5(2+3)+3z= | | 5(y+4)=6(y-4) | | x^2+X^2=1 | | 5x+2x=2x-10 | | y^2+11y=12 | | 3y+30=-y+14 | | 3y+30=-y+13 | | 6m+2m+3=11 | | h+2(h-1)+3=22 | | x+238y=2379 | | 6p+2(2p+3)=16 | | -9=6h+2h+7 | | x+(2x-1)+(3x-4)=27 |